Growth Surprises and Synchronized Slowdowns in Emerging Markets : An Empirical Investigation - Fayad, Ghada (IMF Working Papers; Working Paper ;, 2014)
Output growth has slowed in several emerging markets since 2011-a remarkable feature for a non-crisis period in EMs. Such synchronized slowdowns were largely unanticipated by scholars and forecasters alike. In this paper we attempt to shed light on the main drivers of growth surprises and synchronized slowdowns in emerging markets post-global financial crisis. We find that lower trading partner demand was a key external factor in explaining these events during 2011-13, and that changes in external financing conditions have yet to play a role in EMs' growth. On the domestic front, the withdrawal of the fiscal stimulus put in place right after the Lehman collapse is a relevant aspect in these episodes, compounding the effect of the weaker external demand. Idiosyncratic factors, such as structural bottlenecks with the potential to impair growth in a more lasting fashion, also seem to partly explain these events, as reflected in the larger residuals found in regression-based estimates for certain countries.